Combined application of plant growth-promoting bacteria and iron oxide nanoparticles ameliorates the toxic effects of arsenic in Ajwain (Trachyspermum ammi L.) - Sun, Yan; Ma, Li; Ma, Jing; Li, Bingkun; Zhu, Yanfeng; Chen, Fu (Frontiers in Plant Science, 2022)
Soil contamination by heavy metals is a major threat to the agricultural productivity. Even though, the plant growth promoting bacteria (PGPB) and nanoparticles are the major sources to alleviate the metal toxicity but these were neglected over the years in alleviating Arsenic (As)-induced metal toxicity. Therefore, this study was conducted to investigate the impact of different As levels (0 μM, 50 and 100 μM) on the growth indices, photosynthetic characteristics, nutritional profile, anatomical structure of various membrane bounded organelles, enzymatic potential and their related transcript levels followed by mitigation of As toxicity by Providencia vermicola (5 and 10 ppm) and iron oxide nanoparticle (FeO−NPs) (50 and 100 mg L−1) in Ajwain (Trachyspermum ammi L.). Our results demonstrated that the plants grown in As-polluted soil displayed inhibition in growth, photosynthetic characters, and nutritional profile. The ultra-structure of various membrane bounded organelles exhibited abrupt destruction after As-induced oxidative stress. Further, the enhancement in oxidative stress indicators, proline, organic acid exudation, endogenous As contents, enzymatic and non-enzymatic antioxidants and their respective genes expression were observed in both organs (roots and shoots) of T. ammi following As treatment. However, a combined application of PGPB (P. vermicola) and FeO-NPs displayed a substantial recovery in As-stressed T. ammi plants. In contrast to PGPB (P. vermicola), the FeO-NPs was more helpful in alleviating the As-induced oxidative damage in T. ammi seedlings. Taken altogether, it can be proposed that the combined application P. vermicola and FeO-NPs are significant in reducing the metal-induced toxicity in metal-prone places.